English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-10 06:45:24 · 6 answers · asked by Katy J 1 in Science & Mathematics Mathematics

6 answers

x=ln(47)

2006-12-10 06:48:44 · answer #1 · answered by Peeps 3 · 0 0

Steps to do this problem.

(1) The base of the exponent becomes the base of the log.
(2) The answer goes inside the log.
(3) What remains is the answer.

Step #1 is the most important and the most easy to remember.

"The base of the exponent becomes the base of the log.
In this case, the base of our exponent is e.

log [base e] (?) = (?)

"The answer goes inside the log."

The answer on the right hand side, 47, now becomes part of the log.

log [base e] (47) = ?

"What remains is the answer."
The exponent is what remains, and hence becomes the answer to the log.

log [base e] (47) = x

Remember that log [base e] has a special name: ln

ln (47) = x

2006-12-10 06:50:02 · answer #2 · answered by Puggy 7 · 1 0

log e 47=x

2006-12-10 06:51:39 · answer #3 · answered by abcde12345 4 · 0 0

e^x = 47
log(e)47 = x
x = ln(47)

2006-12-10 06:54:06 · answer #4 · answered by Sherman81 6 · 0 0

e^x=47
when u want to bring the exponent to the right side, u have to ln right side..then x will be brought down...
x=ln 47

2006-12-10 06:54:41 · answer #5 · answered by charmed_ones710 2 · 0 0

e^x=47

x = ln 47

2006-12-10 06:48:28 · answer #6 · answered by Luiz S 7 · 0 0

fedest.com, questions and answers